Pengaruh Good Corporate Governance Terhadap Nilai Perusahaan Dengan Kinerja Keuangan Sebagai Variabel Mediasi - Elizabet Desi Astuti; Saring Suhendro (Jurnal Mutiara Ilmu Akuntansi, 2024)
This research aims to determine the effect of good corporate governance on company value with financial performance as a mediating variable in manufacturing companies listed on the Indonesia Stock Exchange in the 2017-2021 period. This research is a type of quantitative research that uses a sample of 652 data obtained from 154 manufacturing companies. The technique for analyzing data in this research uses the classic assumption test, path analysis, and hypothesis testing with the f test, t test, and coefficient of determination test. Based on the results of data analysis, it can be concluded that (1) institutional ownership has a negative effect on company value, (2) managerial ownership has a negative effect on company value, (3) institutional ownership has a positive effect on financial performance, (4) managerial ownership has no effect on financial performance , (5) financial performance has a positive effect on company value, (6) institutional ownership has a positive effect on company value through financial performance, (7) managerial ownership has a positive effect on company value through financial performance.